Settlers, liberty, and empire the roots of early American political theory, 1675-1775 - Yirush, Craig, 1968- (Cambridge University Press, 2011)
"Settlers, Liberty, and Empire traces the emergence of a revolutionary conception of political authority on the far shores of the eighteenth-century Atlantic world. Based on the equal natural right of English subjects to leave the realm, claim indigenous territory, and establish new governments by consent, this radical set of ideas culminated in revolution and republicanism. But unlike most scholarship on early American political theory, Craig Yirush does not focus solely on the revolutionary era of the late eighteenth century. Instead, he examines how the political ideas of settler elites in British North America emerged in the often-forgotten years between the Glorious Revolution in America and the American Revolution against Britain. By taking seriously an imperial world characterized by constitutional uncertainty, geo-political rivalry, and the ongoing presence of powerful Native American peoples, Yirush provides a long-term explanation for the distinctive ideas of the American Revolution"--